Conservative accounting before equity offerings and its implications on stock returns : An empirical study on the Egyptian stock market - Kholoud Abdelkareem Mahmoud Hussein; Ashraf Mahmoud Kadry Elsharkawy; Hala Abdelnaby Abdelfattah (Cairo : Kholoud Abdelkareem Mahmoud Hussein, 2016)
The main objective of this research is to examine the impact of conservative financial reporting on the announcement effect of secondary public offerings (SPO) in the Egyptian stock market. Specifically, this research aims to investigate empirically: first; the market reaction to the announcement of SPO, second; the individual effects of each type of accounting conservatism- conditional and unconditional conservatism-on the firm's stock performance at the announcement of SPO, and finally; the relationship between accounting conservatism and information asymmetry. The empirical data were drawn from a sample of 79 SPOs for the period 2006- 2014 in the Egyptian Exchange. The event study methodology and multiple regression analysis are used to test the research hypotheses. The results indicate that: first, there is a significant negative abnormal return around the announcements of SPOs. Second, there is a positive association between accounting conservatism and the SPO announcement returns. Third, the relationship between accounting conservatism and SPO announcement returns is more pronounced for firms with high information asymmetry. Finally, conservatism is an efficient mechanism that mitigates information asymmetry problems. The research findings support the proponents of accounting conservatism who argue that the absence of conservatism will harm the financial reporting quality
Thesis (Ph.D.) - Cairo University - Faculty of Commerce - Department of Accounting
Issued also as CD
Keywords: Accounting conservatism; Information asymmetry; Secondary public offerings